Analysis of The Application of The STEAM Approach to Learning In Indonesia: Contributions to Physics Education - Mohd Zaidi Bin Amiruddin; Dhela Rochmatul Magfiroh; Irma Savitri; Sitti Maizatul Iqma Binti Rahman (Indonesia Emerging Literacy Education, 2022)
Optimizing the learning process in achieving student development requires a special strategy in learning. The strategy can be run by applying the STEAM learning model. The STEAM learning process is expected to prepare the next generation to be ready to face the times, helping to develop innovations in life. The purpose of this study was to analyze the application of STEAM learning in Indonesia, especially the contribution to physics education. The method used in this paper is descriptive qualitative through the study of relevant literature with the objectives of the research conducted. The result of this study is that STEAM can be integrated into various learning subjects and levels of education. In addition, the application of STEAM can help develop the skills of students in the 21st century along with technological developments and increasing demands in modern times. In physics learning, the implementation of STEAM can make students actively involved in the teaching and learning process of physics. Students will be involved in ongoing learning and will assist students in finding solutions to the problems given. This has a positive impact because it can improve creative, critical thinking skills and make it easier for students to understand concepts. The implementation of STEAM in international education is very good, for STEAM learning in Indonesia is still lacking. This is because in implementing STEAM learning, you must have special skills to teach it. Thus, it is very important to develop STEAM starting from human resources and appropriate learning materials.